High Performance Computing for Computational Science - VECPAR 2012 10th International Conference, Kope, Japan, July 17-20, 2012, Revised Selected Papers - Dayde, Michel; Marques, Osni; Nakajima, Kengo (Theoretical Computer Science and General Issues,, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 10th International Conference on High Performance Computing for Computational Science, VECPAR 2012, held in Kope, Japan, in July 2012. The 28 papers presented together with 7 invited talks were carefully selected during two rounds of reviewing and revision. The papers are organized in topical sections on CPU computing, applications, finite element method from various viewpoints, cloud and visualization performance, method and tools for advanced scientific computing, algorithms and data analysis, parallel iterative solvers on multicore architectures.